A Comparative Retrospective Study of Poisoning Cases in Central, Zonal and District Hospitals - Pokhrel, Deepak; Pant, Sirjana; Pradhan, Anupama; Mansoor, Saffar (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The 582 data collected from Central, Zonal and District level Hospitals, which occurred from Magh 2057 to Poush 2058 produced significant results. Various parameters (age, sex, marital status, time of ingestion, month of occurrence, Agent responsible for the incidence, type of poisoning, outcome and duration of treatment) were analyzed. Similarly the pattern of frequency distribution of the above-mentioned parameter in central, zonal and district level of hospitals were compared. Hypothesis were made and tested. Females were found to be more susceptible to the intentional incidence than male (p = 0.000). Intentional poisoning for unmarried male was found to be more (34%) than for female. On the contrary, intentional poisoning in female was high in case of married subjects (57%)(p = 0.000). The most common type of poisoning causing the intentional attempt was organophosphates (40%) followed by Phosphides (14%). On the other hand unintentional poisoning was most common due to the unclassified and other agents (8%), which were followed by hydrocarbons (6.3%). (p = 0.000). The most common organophosphate used for intentional attempt for poisoning is methyl parathion (31%) when compared with other groups of organophosphates (26%). Sedative and hypnotics were the most common type of drugs (43%) used for intentional attempt. Nighttime incidence was more frequent (31%). Homicidal poisoning occurring in both central and district hospital were equal being 3.6% of the total types of attempt of incidence. Most of the cases as obvious were found to be cured (84.8% out of total cases). The zonal hospital shows the highest cure rate (89.2%) followed by district hospital (74.2%)-the comparison however excludes central level hospitals. The mortality however is similar in both hospitals (4.4% and 4.5% respectively in zonal and district hospitals). Accidental intake of hydrocarbon was found to be most frequent in the children (33%) while intentional intakes of other agents were more frequent in adults (97%). The rainy season was the most common season for the attempt of intentional incidence (47.8%) adding to mortality. The most common age group of subjects exposed to intentional attempt that adds to the mortality is 15-24 years (39.1%). The TYPE, primarily adding to mortality was intentional intake (91.3%) (p = 0.008). Most of the intentional incidence adding to mortality is caused by organophosphates (66.7%) followed by Phosphides (19%). Subjects between age group 15-24 are more likely to cause the intentional exposure (44%) while children below five years are more likely to cause accidental exposure (6%) (p = 0.000). Seasonal comparison showed a high incidence in rainy season (24%) as compared to that of autumn (23%). Key words: Central Hospital; Zonal Hospital; District Hospital; Aluminium Phosphide; Intentional Poisoning. DOI: 10.3126/kuset.v4i1.2882 Kathmandu University Journal of Science, Engineering and Technology Vol.4, No.1, September 2008, pp 40-48